Reseña: Cómo hacen los pobres para sobrevivir, de Auyero, Javier y Servián, Sofía (Desarrollo, Estado y Espacio, 2023)
Reseña: Cómo hacen los pobres para sobrevivir, de Auyero, Javier y Servián, Sofía
Keywords: reseña